Impact of The Covid-19 Pandemic On Egg Market Integration And Price Transmission In Indonesia - Irawan, Andi (BIMA Journal (Business, Management, & Accounting Journal), 2025)
Purpose: This study aims to examine the impact of the COVID-19 pandemic on the egg market by analyzing changes in market integration and price transmission across major producing and consuming regions in Indonesia. Methodology: The research employs a quantitative empirical approach using secondary time-series data on egg prices from eight provinces, covering pre-pandemic (July 2017–February 2020) and pandemic (March 2020–August 2021) periods. Econometric analyses were conducted using the Augmented Dickey-Fuller (ADF) test, Johansen cointegration method, and Variance Decomposition within a Vector Error Correction Model (VECM) framework to assess market integration and price transmission dynamics. Results: The findings indicate a significant decline in market integration during the COVID-19 pandemic compared to the pre-pandemic period, reflecting weaker inter-market linkages. Price transmission among regional markets also decreased, suggesting reduced efficiency in transmitting price signals during the crisis. Novelty: This study provides a comparative econometric assessment of market behavior before and during a major global health crisis. Findings: The COVID-19 pandemic disrupted the stability and efficiency of the egg market, affecting both market connectivity and price responsiveness. Originality: The originality of this research lies in its multi-regional time-series analysis focusing on essential food commodities during a pandemic context. Conclusions: Strengthening market coordination and supply chain resilience is crucial to maintaining price stability and food accessibility during future crises. Type of Paper: Empirical Quantitative Study.